2013
DOI: 10.2459/jcm.0b013e32835853a3
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and ECG patterns of isolated right ventricular infarction with nondominant right coronary artery

Abstract: The prevalence of isolated right ventricular infarction is 0.4-2.4% in autopsy series and may occur by at least three different mechanisms, of which occlusion of a nondominant right coronary artery is reviewed here. Although rare, as oxygen demand/supply of the right is lower than that of the left ventricle, due to the smaller muscular mass, and it has a good prognosis, sudden death and cardiac rupture have been reported. Differential diagnosis with anterior infarction is needed. ECG may help but specific crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…8 Another group reported that decreasing STE from lead V 1 to lead V 3 is a pattern specific to isolated RV myocardial infarction. 9 We observed this pattern in Patient 2, but not in Patient 1. The cases that we have described illustrate the rare occurrence of isolated anterior STE correlated with acute RV marginal branch or proximal nondominant RCA occlusion causing acute RV myocardial infarction.…”
Section: Discussionmentioning
confidence: 54%
“…8 Another group reported that decreasing STE from lead V 1 to lead V 3 is a pattern specific to isolated RV myocardial infarction. 9 We observed this pattern in Patient 2, but not in Patient 1. The cases that we have described illustrate the rare occurrence of isolated anterior STE correlated with acute RV marginal branch or proximal nondominant RCA occlusion causing acute RV myocardial infarction.…”
Section: Discussionmentioning
confidence: 54%
“…The second main pattern is STE in anterior leads. This ECG pattern includes decreasing STE from V 1 /V 2 to V 4 /V 5 with no apparent Q waves and no reciprocal STD in inferior leads . When IRVMI leads to RV enlargement, there will be clockwise transposition of the heart, resulting in STE in anterior leads.…”
Section: Discussionmentioning
confidence: 99%
“…This ECG pattern includes decreasing STE from V 1 /V 2 to V 4 /V 5 with no apparent Q waves and no reciprocal STD in inferior leads. 5,6 When IRVMI leads to RV enlargement, there will be clockwise transposition of the heart, resulting in STE in anterior leads. Because V 1 is located directly over the RV, STE in V 1 is greater than that in V 2 and V 3 .…”
Section: Challenges In Clinical Electrocardiographymentioning
confidence: 99%
“…Kejadian tersebut dapat terjadi akibat: 1) penyumbatan proksimal RCA dominan dengan adanya aliran darah kolateral dari arteri koroner kiri ke kanan; 2) sumbatan terisolasi dari arteri cabang marginal setelah intervensi koroner primer perkutan; dan 3) sumbatan pada arteri koroner kanan (RCA) non-dominan. 14…”
Section: Gambaran Elektrokardiografi Infark Ventrikel Kanan Tunggal/ Terisolasiunclassified
“…Keduanya dapat muncul sebagai elevasi segmen ST pada sadapan anterior. 14 Parameter elektrokardiografi spesifik diperlukan untuk diagnosis infark ventrikel kanan tunggal/terisolasi pada RCA nondominan, meliputi: 1) ST elevasi berbentuk kubah (dome-like) dan menurun dari V1 hingga V3; 2) normalisasi cepat segmen ST dan tidak terdapat evolusi gelombang Q dari V1 hingga V3; 3) ST elevasi pada sadapan kanan yang butuh dieksplorasi; 3) tidak adanya ST depresi pada aVL; dan 4) tidak adanya ST elevasi pada sadapan inferior (II, III, aVF).…”
Section: Gambar 6 Algoritma Ekg Untuk Penentuan Arteri Koroner Yang Tersumbatunclassified